Life on the boundary: Environmental factors as drivers of habitat distribution in the littoral zone. (5th April 2016) - Cefalì, Maria Elena; Cebrian, Emma; Chappuis, Eglantine; Pinedo, Susana; Terradas, Marc; Mariani, Simone; Ballesteros, Enric
Abstract: The boundary between land and sea, i.e. the littoral zone, is home to a large number of habitats whose distribution is primarily driven by the distance to the sea level but also by other environmental factors such as littoral's geomorphological features, wave exposure, water temperature or orientation. Here we explore the relative importance of those major environmental factors that drive the presence of littoral rocky habitats along 1100 Km of Catalonia's shoreline (Spain, NW Mediterranean) by using Geographic Information Systems and Generalized Linear Models. The distribution of mediolittoral and upper infralittoral habitats responded to different environmental factors. Mediolittoral habitats showed regional differences drawn by sea-water temperature and substrate type. Wave exposure (hydrodynamism), slope and geological features were only relevant to those mediolittoral habitats with specific environmental needs. We did not find any regional pattern of distribution in upper infralittoral habitats, and selected factors only played a moderate role in habitat distribution at the local scale. This study shows for the first time that environmental factors determining habitat distribution differ within the mediolittoral and the upper infralittoral zones and provides the basis for further development of models oriented at predicting the distribution of littoral marine habitats. Graphical abstract: Highlights: We study habitat-environment relationships at a regional scale. We used high resolution datasets for 29 littoral habitats and 7 environmental factors. Water temperature is the main factor driving mediolittoral habitat distributions. Wave exposure is the main factor related to upper infralittoral habitat distributions.